Learning Styles and Teaching Styles: Inovação educacional por meio de espaços e metodologias de ensino e aprendizagem em ambientes STEAM - Delgado Rodríguez, Santiago; García Fandiño, Rebeca; González García, Ricardo (Journal of Learning Styles, 2023)
A wide range of global research highlights the importance of using technologies effectively in educational settings, highlighting that the achievement of educational objectives is directly related to this practice (Brown et al., 2020). The active participation of students in STEAM educational projects is as essential as exploring the influence that technological advances and new teaching materials have on learning. It is essential that such STEAM initiatives or educational environments be aligned with the development of cutting-edge methodologies that integrate solid theories and apply evaluation strategies and techniques in accordance with the technological tools in use, thus guaranteeing their effective implementation (Pellas et al., 2019). . Likewise, it is critical to take into account the ethical principles related to the use of technology in STEAM education, considering the potential moral dilemmas and responsibilities linked to the use of these innovative educational resources, as well as the strategies necessary for their correct, responsible and equitable in teaching.